Watershed Continuum Monitoring Approach: combining multiple water quality patterns along stream and river flowpaths to track sources, pathways, and processing of pollutants - Sujay S. Kaushal; Ashley E. Mon; Stanley B. Grant; Paul M. Mayer; Aaron J. Porter; Andrew J. Sekellick; Jason H. Chase; Shantanu V. Bhide; John D. Jastram; Tamara A. Newcomer-Johnson; Sydney A. Shelton; Alexis M. Yaculak; et al. (Ecological Engineering, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Celebrating the fifth edition of the International Symposium on Fungal Stress – ISFUS, a decade after its 2014 debut - Alene Alder-Rangel; Amanda E.A. Rangel; Arturo Casadevall; Asiya Gusa; Chaoyang Xue; Charles M. Boone; Chris Todd Hittinger; Claudio A. Masuda; Consuelo Olivares-Yañez; Deborah Bell-Pedersen; Erica J. Washington; Gerhard Braus; et al. (Fungal Biology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Novel Curvularia species causing disseminated phaeohyphomycosis in a dog - Jared A. Jaffey; Connie F. Cañete-Gibas; Nathan P. Wiederhold; Carmita J. Sanders; Jason D. Struthers; Annalise Black; BinXi Wu; Kara S. Thomas; Patricia Bennett; Jessica Watt (Topics in Companion Animal Medicine, 2025)

Assessing impacts of a notorious invader (common carp Cyprinus carpio) on Australia's aquatic ecosystems: Coupling abundance-impact relationships with a spatial biomass model - Benjamin G. Fanson; Robin Hale; Jason D. Thiem; Jarod P. Lyon; John D. Koehn; Andrew F. Bennett; Ivor Stuart (Biological Conservation, 2024)

Lithospheric hydrous pyroxenites control localisation and Ni endowment of magmatic sulfide deposits - Isra S. Ezad; Daryl E. Blanks; Stephen F. Foley; David A. Holwell; Jason Bennett; Marco L. Fiorentini (Mineralium Deposita, 2024)

Turning up the volume: How root branching adaptive responses aid water foraging - Poonam Mehra; Rebecca Fairburn; Nicola Leftley; Jason Banda; Malcolm J. Bennett (Current Opinion in Plant Biology, 2023)

Dose metric evaluation of a cell-based bioassay for assessing the toxicity of metals to Dugong dugon: Effect of metal-media interactions on exposure concentrations - David Bailey; Kimberly A. Finlayson; Gulsah Dogruer; William W. Bennett; Jason P. van de Merwe (Aquatic Toxicology, 2023)

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Governance in the Face of Extreme Events: Lessons from Evolutionary Processes for Structuring Interventions, and the Need to Go Beyond - Simon A. Levin; John M. Anderies; Neil Adger; Scott Barrett; Elena M. Bennett; Juan Camilo Cardenas; Stephen R. Carpenter; Anne-Sophie Crépin; Paul Ehrlich; Joern Fischer; Carl Folke; Nils Kautsky; et al. (Ecosystems, 2022)

Thermal optima of gross primary productivity are closely aligned with mean air temperatures across Australian wooded ecosystems - Alison C. Bennett; Stefan K. Arndt; Lauren T. Bennett; Jürgen Knauer; Jason Beringer; Anne Griebel; Nina Hinko‐Najera; Michael J. Liddell; Daniel Metzen; Elise Pendall; Richard P. Silberstein; Timothy J. Wardlaw; et al. (Global Change Biology, 2021)
Gross primary productivity (GPP) of wooded ecosystems (forests and savannas) is central to the global carbon cycle, comprising 67%–75% of total global terrestrial GPP. Climate change may alter this flux by increasing the frequency of temperatures beyond the thermal optimum of GPP ( T opt ). We examined the relationship between GPP and air temperature (Ta) in 17 wooded ecosystems dominated by a single plant functional type (broadleaf evergreen trees) occurring over a broad climatic gradient encompassing five ecoregions across Australia ranging from tropical in the north to Mediterranean and temperate in the south. We applied a novel boundary‐line analysis to eddy covariance flux observations to (a) derive ecosystem GPP–Ta relationships and T opt (including seasonal analyses for five tropical savannas); (b) quantitatively and qualitatively assess GPP–Ta relationships within and among ecoregions; (c) examine the relationship between T opt and mean daytime air temperature (MDTa) across all ecosystems; and (d) examine how down‐welling short‐wave radiation (Fsd) and vapour pressure deficit (VPD) influence the GPP–Ta relationship. GPP–Ta relationships were convex parabolas with narrow curves in tropical forests, tropical savannas (wet season), and temperate forests, and wider curves in temperate woodlands, Mediterranean woodlands, and tropical savannas (dry season). Ecosystem T opt ranged from 15℃ (temperate forest) to 32℃ (tropical savanna—wet and dry seasons). The shape of GPP–Ta curves was largely determined by daytime Ta range, MDTa, and maximum GPP with the upslope influenced by Fsd and the downslope influenced by VPD. Across all ecosystems, there was a strong positive linear relationship between T opt and MDTa (Adjusted R 2 : 0.81; Slope: 1.08) with T opt exceeding MDTa by >1℃ at all but two sites. We conclude that ecosystem GPP has adjusted to local MDTa within Australian broadleaf evergreen forests and that GPP is buffered against small Ta increases in the majority of these ecosystems.

Genetic analysis of wheat (Triticum aestivum) adaptation to heat stress - Paul Telfer; James Edwards; Adam Norman; Dion Bennett; Alison Smith; Jason A. Able; Haydn Kuchel (Theoretical and Applied Genetics, 2021)

The relationship between pain, analgesics and survival in patients with advanced cancer; a secondary data analysis of the international European palliative care Cancer symptom study. - Jason W Boland; Victoria Allgar; Elaine G Boland; Mike I Bennett; Stein Kaasa; Marianne Jensen Hjermstad; Miriam Johnson (European Journal of Clinical Pharmacology, 2020)
Purpose Opioids reduce cancer-related pain but an association with shorter survival is variably reported. Aim: To investigate the relationship between pain, analgesics, cancer and survival within the European Palliative Care Cancer Symptom (EPCCS) study to help inform clinical decision making. Methods Secondary analysis of the international prospective, longitudinal EPCCS study which included 1739 adults with advanced, incurable cancer receiving palliative care. In this secondary analysis, for all participants with date of death or last follow up, a multilevel Weibull survival analysis examined whether pain, analgesics, and other relevant variables are associated with time to death. Results Date of death or last follow-up was available for 1404 patients (mean age 65.7 [SD:12.3];men 50%). Secondary analysis of this group showed the mean survival from baseline was 46.5 (SD:1.5) weeks (95% CI:43.6–49.3). Pain was reported by 76%; 60% were taking opioids, 51% non-opioid analgesics and 24% co-analgesics. Opioid-use was associated with decreased survival in the multivariable model (HR = 1.59 (95% CI:1.38–1.84), p < 0.001). An exploratory subgroup analysis of those with C-reactive protein (CRP) measures ( n = 219) indicated higher CRP was associated with poorer survival ( p = 0.001). In this model, the strength of relationship between survival and opioid-use weakened ( p = 0.029). Conclusion Opioid-use and survival were associated; this relationship weakened in a small sensitivity-testing subgroup analysis adjusting for CRP. Thus, the observed relationship between survival and opioid-use may partly be due to tumour-related inflammation. Larger studies, measuring disease activity, are needed to confirm this finding to more accurately judge the benefits and risks of opioids in advanced progressive disease.

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Medial temporal lobe volumes in late-life depression: effects of age and vascular risk factors - Warren D. Taylor; Yi Deng; Brian D. Boyd; Manus J. Donahue; Kimberly Albert; Maureen McHugo; Jason A Gandelman; Bennett A. Landman (Brain Imaging and Behavior, 2020)

Climate change, hydrology, and fish morphology: predictions using phenotype-environment associations - Matt J. Michel; Huicheng Chien; Collin E. Beachum; Micah G. Bennett; Jason H. Knouft (Climatic Change, 2017)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Erratum to: Signaling Pathways Involved in 1-Octen-3-ol-Mediated Neurotoxicity in Drosophila melanogaster: Implication in Parkinson’s Disease - Arati A. Inamdar; Prakash Masurekar; Muhammad Hossain; Jason R. Richardson; Joan W. Bennett (Neurotoxicity Research, 2014)

Signaling Pathways Involved in 1-Octen-3-ol-Mediated Neurotoxicity in Drosophila melanogaster: Implication in Parkinson’s Disease - Arati A. Inamdar; Prakash Masurekar; Muhammad Hossain; Jason R. Richardson; Joan W. Bennett (Neurotoxicity Research, 2014)

Evolutionary replacement of obligate symbionts in an ancient and diverse insect lineage - Ryuichi Koga; Gordon M. Bennett; Jason R. Cryan; Nancy A. Moran (Environmental Microbiology, 2013)
Summary Many insect groups depend on ancient obligate symbioses with bacteria that undergo long‐term genomic degradation due to inactivation and loss of ancestral genes. Sap‐feeding insects in the hemipteran suborder A uchenorrhyncha show complex symbioses with at least two obligate bacterial symbionts, inhabiting specialized host cells (bacteriocytes). We explored the symbiotic relationships of the spittlebugs ( A uchenorrhyncha: C ercopoidea) using phylogenetic and microscopy methods. Results show that most spittlebugs contain the symbionts S ulcia muelleri ( B acteroidetes ) and Z inderia insecticola ( B etaproteobacteria ) with each restricted to its own bacteriocyte type. However, the ancestral Z inderia symbiont has been replaced with a novel symbiont closely related to S odalis glossinidius ( E nterobacteriaceae ) in members of the ecologically successful spittlebug tribe P hilaenini. At least one spittlebug species retains S ulcia and Z inderia , but also has acquired a S odalis ‐like symbiont, possibly representing a transitional stage in the evolutionary succession of symbioses. Phylogenetic analyses including symbionts of other A uchenorrhyncha lineages suggest that Z inderia , like S ulcia , descends from an ancestral symbiont present in the common ancestor of A uchenorrhyncha. This betaproteobacterial symbiont has been repeatedly replaced by other symbionts, such as the S odalis ‐like symbiont of spittlebugs. Symbiont replacement may offer a route for hosts to escape dependence on an ancient, degraded and potentially inefficient symbiont.

Likely Population-Level Effects of Contaminants on a Resident Estuarine Fish Species: Comparing Gillichthys mirabilis Population Static Measurements and Vital Rates in San Francisco and Tomales Bays - Catherine R. McGourty; James A. Hobbs; William A. Bennett; Peter G. Green; Hyun-Min Hwang; Naoaki Ikemiyagi; Levi Lewis; Jason M. Cope (Estuaries and Coasts, 2009)

A checklist for ecological management of landscapes for conservation - David Lindenmayer; Richard J. Hobbs; Rebecca Montague‐Drake; Jason Alexandra; Andrew Bennett; Mark Burgman; Peter Cale; Aram Calhoun; Viki Cramer; Peter Cullen; Don Driscoll; Lenore Fahrig; et al. (Ecology Letters, 2008)
The management of landscapes for biological conservation and ecologically sustainable natural resource use are crucial global issues. Research for over two decades has resulted in a large literature, yet there is little consensus on the applicability or even the existence of general principles or broad considerations that could guide landscape conservation. We assess six major themes in the ecology and conservation of landscapes. We identify 13 important issues that need to be considered in developing approaches to landscape conservation. They include recognizing the importance of landscape mosaics (including the integration of terrestrial and aquatic areas), recognizing interactions between vegetation cover and vegetation configuration, using an appropriate landscape conceptual model, maintaining the capacity to recover from disturbance and managing landscapes in an adaptive framework. These considerations are influenced by landscape context, species assemblages and management goals and do not translate directly into on‐the‐ground management guidelines but they should be recognized by researchers and resource managers when developing guidelines for specific cases. Two crucial overarching issues are: (i) a clearly articulated vision for landscape conservation and (ii) quantifiable objectives that offer unambiguous signposts for measuring progress.

An Approach to Predict Risks to Wildlife Populations from Mercury and Other Stressors - Diane Nacci; Marguerite Pelletier; Jim Lake; Rick Bennett; John Nichols; Romona Haebler; Jason Grear; Anne Kuhn; Jane Copeland; Matthew Nicholson; Steven Walters; Wayne R. Munns (Ecotoxicology, 2005)

Survival of Salmonella Species in River Water - Jorge W. Santo Domingo; Stephen Harmon; Jason Bennett (Current Microbiology, 2000)

Novel Chitinolytic Enzymes with Biological Activity Against Herbivorous Insects - Roxanne M. Broadway; Carmenza Gongora; Wendy C. Kain; John P. Sanderson; Jose A. Monroy; K. C. Bennett; Jason B. Warner; Michael P. Hoffmann (Journal of Chemical Ecology, 1998)